The commitment of farmers to traditional and hybrid cooperatives: Empirical evidence over a six-year period - Rebecca Hansen; Sebastian Hess; Jerker Nilsson; Petri Ollila (Annals of Public and Cooperative Economics, 2024)
This study investigates the commitment of farmer members to traditional and hybrid cooperatives, and examines how and why their commitment has changed over time. The empirical basis consists of three surveys of representative samples of Finnish farmers conducted in 2010, 2013 and 2016. Dairy cooperatives in Finland have a traditional organizational form. Animal breeders deliver to hybrid cooperatives that have some external investors, but farmers have the majority of the votes. In both industries, the farmers are committed to their cooperatives and increasingly so over the years. This is particularly true of dairy farmers. However, the members' commitment is based more on their satisfaction with the cooperatives' business activities rather than on any cohesion within the cooperative societies. One explanation for this is that primary agriculture is becoming more consolidated, with fewer but larger farms whose owners are business oriented and professional.
Keywords: 330; cooperative ideology; Finland; horizontal integration; membership motive; ordered probit; sample selection; vertical integration